Currícul(o/a)rizando a cidade : enredamentos possíveis das práticaspolíticas dos/as praticantespensantes do programa educação em tempo integral no território-cidade de Vitória-ES - Figueiredo, Ricardo (2015)
The enunciation of the problem that led to the investigation of processuality linked up to our experience in discussion, implementation and evaluation of the Education Full-Time Program in the Territory-City of Vitória-ES. Through this, we seek to understand engendered political practices engendered by thinking practitioners of Education Program Full Time in procedurals invention curricula practiced in the four primary schools located in different regions of the municipality, in order to arrest the movement experienced by the thinking practitioners of th e program, in different times and spaces of enabling activities. To capture the tessitura and possible entanglements in relation to the political practices of the thinking practitioners of Education Program in Full Time, in the way of inventing practiced curricul a, adopted as a theoretical, epistemological and methodological perspective the contribution of the conditions of mapping, analysis of school everyday, from the understanding that were composed by fragments and tessitura of the networks that are woven by ordinary subjects (CERTEAU, 2011), in possible and situations that led to the invention of practiced curricula. Still, for the production of data, use of resources of photographs, filming and conversations networks that implicated and involved significant number of practitioners of the program, working in different times and enabling spaces of multiple practices curriculum policies. However, that research is based on the contribution of / the following intercessors / as: Barros and Kastrup (2009), Cavaliere (2002, 2009), Certeau (2003, 2009, 2011), Carvalho (2005, 2007, 2008, 2009, 2012), Coelho (2009), Ferraço (2003, 2005, 2006, 2008, 2011, 2012), Moll (2009, 2012) and Oliveira (1998, 2003, 2008a, 2008b, 2011, 2012) in the tessitura of inventive ways of practice and thinking curriculum practiced by / the thinking practitioners of Education Program in Full Time intersecting by the production of subjectivities. Considering that the experienced political practices by/the thinking practitioners of Education Program in Ful l Time in the fabric of the prevailing curricula express manifestations and curricular inventions, from the ways in which they have, used and consumed time the possible areas of viability of experienced practices political. Still, the tessitura of political practices of the curricula practiced on/of the Education Program in Full Time, in different contexts, include singularities of trajectories for each of the four school units viability of Education Program in Full Time, consisting of movements tactical of each individual. Therefore, the fabric of the curriculum practiced in school everyday, support the idea, that the invention of the curriculum, comes from complex relationships, plural and multiple involving different thinking practitioners program. Both t hose working in schools, as in other areas and enabling 21 times of activities, from the circumstances of the established networks. Thus, it is possible to understand that "there is no single curriculum in school," nor "a unique way of doing and feeling curriculum" in schools, especially those of viability of Education Program in Full Time.